Peran Ganda Perempuan Pekerja Rumput Laut dalam Keluarga di Kabupaten Bantaeng - Irwan, Irwan; Nur, Hasruddin (Phinisi Integration Review, 2021)
Research objectives: 1. To determine the dual role of women seaweed farmers in the family of seaweed farmers in Pa'jukang sub-district, Bantaeng Regency, 2. To find out how the dual roles of women seaweed farmers in the family of seaweed farmers in managing the house (domestic sector) and carry out their roles outside the home (public sector) 3. To determine the positive and negative impacts of the dual role of women seaweed farmers in the family. The type of research used is descriptive qualitative, through data collection techniques in the form of observation, interviews, and documentation. By using data analysis techniques in the form of data reduction, data presentation, and conclusion. The activity plan in realizing the goals to be achieved, this research is planned to take place from September to December 2020 with the following stages: 1. The researcher conducted a survey in the Pa'jukakang sub-district, Bantaeng Regency, 2. The researcher prepared the materials used to retrieve the data- data related to research objectives, both secondary data and primary data, 3. Direct researchers to take data using a list of questions for informants, 4. Researchers inventory the problem of women's dual role in the seaweed farming community, and 5. The results of the data obtained processed and analyzed, in order to find the dual role of women lauat farmers, managing time in managing the domestic and public sectors, and the positive and negative impacts of the dual roles of women seaweed farmers.